Experimental model for transanal endorectal pull-through surgery. Technique of de la Torre and Ortega - Takegawa, B.; Ortolan, Erika Veruska Paiva [UNESP]; Rodrigues, A. M.; Chambo, F.; Paula, FDE (W B Saunders Co, 2005)
Background: We describe an experimental model for transanal endorectal pull-through surgery using the method of de]a Torre and Ortega that can be used for training purposes in experimental laboratories.Methods: Ten rabbits were submitted to the transanal endorectal pull-through technique of de la Torre and Ortega. Animals were randomly selected in the Botucatu School of Medicine experimental laboratory. Animals weighted between 2800 and 4400 g. Colons were not prepared, and antibiotic therapy was not used; dipyrone(1) was administered postoperatively for analgesic purposes. We standardized resected segment size, recorded surgical time, and observed Survival and possible complications for 1 month.Results: All animals survived the initial follow-up period without infection. Bowel movements returned quickly, and all animals were evacuating regularly within the first 24 hours. Mean surgical time was 48.6 minutes.Conclusions: the experimental model proposed in this study is very useful for training and improving surgical techniques using the method of de la Torre and Ortega. The rabbit is an excellent animal for this surgery because of its size and postoperative resistance. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: endorectal pull-through; Hirschsprung disease; experimental model